Changes in agronomic tolerance of several genotypes of maize to waterlogging. Issue 3 (July 2021) - Muliadi, A; Yustisia,; Nur, A; Azrai, M
Abstract: Waterlogging is a major factor in reducing crop yields. To increase plant productivity in temporarily waterlogged soils, the development of waterlogging tolerant lines is needed. This study aims to determine the genotype of maize that is tolerant of waterlogging and morphological characters that can be used for selection criteria. The experiment was carried out in greenhouse of Maros experimental farm. A total of 40 maize genotypes and 2 check varieties, namely MGold and Bima 19, were tested using a randomized block design, 3 replications. Screening was carried out in 2 conditions, namely waterlogged and normal conditions. Based on the waterlogging sensitivity index (WSI), the WSI value was different for each variable. The results of the main component analysis show that the variables that had a major influence on the diversity of tolerance of maize genotypes to waterlogging stress was number of root so that they could be used as character selection in waterlogging stress. Genotypes classified as tolerant are N29/B-2-2, N29/B2-4, B2/N29-5, JH45/B18-3, JH45/B18- 5, B18/JH-45-1, B18/JH-45-2, B18/JH45-4, B18/JH45-5, BM-9/P36-2, BM-9/P36-4, BM- 9/P36-5, and NK7328/HJ28-5.